Pengaruh Liberalisasi Perdagangan Terhadap Ketahanan Pangan di Indonesia - Fian Trinugraha (Green Publisher Indonesia, 2026)
This research examines the impact of trade liberalization on food security in Indonesia. As the country has actively participated in global trade agreements, the liberalization process poses challenges to its agricultural sector, particularly in maintaining food sovereignty. The study identifies key factors, including policy adjustments and international trade agreements, that affect the nation's ability to ensure food availability, accessibility, and stability. Using a qualitative approach, this research analyzes the consequences of these trade agreements on the local agricultural market and the broader implications for food security in Indonesia. The findings suggest that while liberalization promotes economic growth, it also exacerbates vulnerabilities in the food supply chain, highlighting the need for more resilient policies that integrate both food security and sustainable agricultural practices.